2019
DOI: 10.1038/s41598-018-38264-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular layer interneurons shape the spike activity of cerebellar Purkinje cells

Abstract: Purkinje cells receive synaptic input from several classes of interneurons. Here, we address the roles of inhibitory molecular layer interneurons in establishing Purkinje cell function in vivo. Using conditional genetics approaches in mice, we compare how the lack of stellate cell versus basket cell GABAergic neurotransmission sculpts the firing properties of Purkinje cells. We take advantage of an inducible Ascl1CreER allele to spatially and temporally target the deletion of the vesicular GABA transporter, Vg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
107
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 113 publications
(142 reference statements)
10
107
1
Order By: Relevance
“…To test this hypothesis, we used a genetic fate mapping approach to selectively mark basket cells and specifically to highlight the boundaries of their cell membranes with a conditional reporter (Figure 7). We recently showed that an Ascl1 CreERT2 allele can be used to mark basket cells based on their birth date during late embryogenesis (Brown et al, 2019). Ascl1 , also known as Mash1 , encodes a member of the basic helix-loop-helix (BHLH) family of transcription factors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To test this hypothesis, we used a genetic fate mapping approach to selectively mark basket cells and specifically to highlight the boundaries of their cell membranes with a conditional reporter (Figure 7). We recently showed that an Ascl1 CreERT2 allele can be used to mark basket cells based on their birth date during late embryogenesis (Brown et al, 2019). Ascl1 , also known as Mash1 , encodes a member of the basic helix-loop-helix (BHLH) family of transcription factors.…”
Section: Resultsmentioning
confidence: 99%
“…A knock-in allele of CreER into the Ascl1 locus faithfully reports on the differentiation of GABAergic neurons in the cerebellum, and it has a dual function in labeling different subsets of inhibitory neurons at the time of their birth (Sudarov et al, 2011). Here, we crossed the Ascl1 CreERT2 mice to a mouse line that expresses myristoylated GFP (mGFP) in differentiated neurons (Hippenmeyer et al, 2005), but only after recombination is induced upon tamoxifen administration to the mice (Brown et al, 2019). We chose this genetic strategy because oral gavage of tamoxifen to pregnant dams when their embryos are embryonic day (E) 18.5 labels a rich population basket cells with recombination at ∼43% across the entire cerebellum (Brown et al, 2019; the genetic strategy is schematized in Figure 7E), and the mGFP reporter impressively fills the entire axons of even the finest projections in the cerebellum (Sillitoe et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…days and trace their locations and patterns of axon morphogenesis. We used the tamoxifen-inducible Ascl1-CreER line to activate Cre in MLI progenitors at the time of terminal division(Sudarov et al 2011;Brown et al 2019). Consistent with previous studies, tamoxifen (TMX) injection of Ascl1-CreER; Ai4 flox-STOP-TdTomato animals at P0 enriched for the labelling of BCs that innervate the lower ML, while delivery at P4 and P7 marked SC-like cells restricted to the upper ML (…”
mentioning
confidence: 82%